Polarographic Determination of Stability Constant Values of Complexes of Levulinic Acid with Ga(III) and Tl(I) by DeFord and Hume's and Mihailov's Methods - Meena, Suman; Agrawal, Smita; Gupta, O.D. (Asian Journal of Chemistry, 2011)
The reduction of Ga(III) and Tl(I) with levulinic acid has been investigated electrochemically in aqueous medium and the stability constants of complexes have been evaluated. The metal complexes of levulinic acid with ratio as 1:1, 1:2, 1:3 for Ga(III) and 1:1, 1:2 for Tl(I) have been reported. The values of stability constants of complexes of levulinic acid with Ga(III) have log b1 = 2.92, log b2 = 5.74, log b3 = 8.39 and complex of levulinic acid with Tl(I) have log b1 = 2.62, log b2 = 5.58 at 308 K, which have been calculated by DeFord and Hume's method. The mathematical Mihailov's method was also used.